Circadian Disruption and Occupational Toxicants Exposure Affecting the Immunity of Shift Workers During SARS CoV-2 Pandemic - Mohd Fuad, Siti Hanisah; Juliana, Norsham; Mohd Azmi, Nor Amira Syahira; Mohd Fahmi Teng, Nur Islami; Azmani, Sahar; Abu, Izuddin Fahmy; Das, Srijit (Frontiers in Public Health, 2022)
In several regions of the world, the recent Coronavirus Disease-2019 (COVID-19) pandemic outbreak increased morbidity and mortality. The pandemic situation disrupted many workers' previously established lifestyles. The main aim of the present review was to describe the circadian disruption and occupational toxicant exposure affecting the immunity of shift workers during the SARS CoV-2 pandemic. We retrieved pertinent published literature from the Google Scholar, PubMed, and Scopus databases. In the present review, we discuss the circadian rhythm involving the hypothalamic-pituitary-adrenal (HPA) axis at the molecular level, its disruption, occupational toxicant exposure causing immunomodulatory effects, and the role of immunity during the SARS CoV-2 pandemic. The severity of the progression of the viral infection depends on multiple factors affecting immunity. Hence, shift workers may need to be aware of those factors such as circadian rhythm disruption as well as occupational toxicant exposure. The timing of shift workers' energy intake is also important concerning the shift of the workers. The information in the present review may be important for all workers who are at risk during the pandemic. In the absence of any published literature related to association of circadian rhythm disruption with occupational toxicant exposure, the present review may have greater importance.